Amir Ziyadat Allah I Bin Amir Ibrahim I (201-223h/817-838m) Dan Sumbangannya Terhadap Dinasti Aghlabiyya. - Tumiran, Siti Noorasikin (2022)
Amir Ziyadat Allah I bin Amir Ibrahim I is a Muslim leadership figure who has great potential and caliber in administering of Aghlabid Dynasty. His authority was evident due to the success of continuing the legacy of Amir Ibrahim I by expanding and advancing the dynasty to be in line with the progress of other Islamic dynasties at that time. The composition towards complex society of Aghlabid Dynasty was successfully ruled by Amir Ziyadat Allah I who came from a minority group of Arabs. Unfortunately, studies of his prominence and contributions are not highlighted in depth. The prejudicial attitude of some Western writers has given rise to a negative perception of leadership by the amir. This study is to investigate the developments of Aghlabid Dynasty, the background of Amir Ziyadat Allah I and also his contributions towards the dynasty. This study uses a qualitative method approach, through the instrument of literature review and document analysis. The findings of this study revealed Amir Ziyadat Allah I amongst the most important and famous amirs of Aghlabid Dynasty. His greatness as a ruler highlights the authority of the amir so that he can be appointed as a reformist or “mujahid” in his time. Under the administration of Amir Ziyadat Allah I, the dynasty had grown rapidly in political, economic and educational aspects. The establishment of Islam in continental Europe for the second time through the conquest of Sicily was his greatest contribution in the political aspect.